Consumer experience of interactive technology in fashion stores. Issue 12 (16th August 2019) - Siregar, Yuri; Kent, Anthony
Abstract : Purpose: Despite the growth of digital fashion shopping, many consumers regularly visit physical fashion stores. To enable digital interactions in a physical store, many fashion brands have installed interactive technology. However, studies of consumer engagement with interactive technology in fashion stores remain scarce. The purpose of this paper is to explore the experience with interactive technology in fashion stores. Design/methodology/approach: A qualitative user experience design (UXD) approach was employed to address the research question. A combination of methods: protocol analysis, observation and interview, was used to collect the data. A prominent UXD framework was utilised to analyse the data. Findings: There are four themes representing findings: split domain, digital domain merchandise, interactive information and interaction moments. For these, two core concepts were extracted: control over experience via framing and challenges for experience. Originality/value: This research paper infused a new approach that is UXD into the field of fashion marketing. This shows the possibility to amalgamate those contrasting fields. Moreover, this research paper provides insights particularly about the interactions with a technology in fashion stores.